Media Guidance and Shaping of Public Opinion: Mechanisms, Ethics and Influences - Wang, Yichen (Transactions on Social Science, Education and Humanities Research, 2024)
The paper analyzed the role of media in guiding and shaping public opinion and its ethical issues through literature review. The results show that media should take into account many ethical factors in addition to conveying information when guiding public opinion. The first is the responsibility of the media, which is not only the accuracy of information, but also how the media balances commercial interests with the public interest, how they deal with sensitive or controversial issues, how they deal with different views and positions. Accountability is another important ethical consideration. Accountability helps ensure that the media does not abuse its power to guide public opinion and avoids bias and partisanship that mislead the public. At the same time, accountability can encourage the media to handle sensitive issues more carefully and maintain professional and ethical standards. When guiding public opinion, the media should fully consider the ethical factors, not only to achieve objective and fair information dissemination, but also to assume due social responsibilities. When the media guide public opinion, manipulation and freedom of speech are two ethical considerations that cannot be ignored. Manipulation occurs when the media influences public perceptions and attitudes through specific reporting angles, language, or content choices.